From Clicks to Change: The Role of Generation Z in Reshaping Indonesian Politics - Darto Wahidin; Sugiyanto, Sugiyanto; Aidah , Salwa (Universitas Muhammadiyah Makassar, 2025)
In an era marked by democratic volatility, digital polarization, and eroding trust in political institutions, understanding how Generation Z engages with politics in Indonesia has become an urgent scholarly and practical concern. As the largest emerging electoral cohort, their political behavior is likely to shape the trajectory of Indonesian democracy in the coming decades. This study aims to identify the concrete forms of political engagement adopted by Generation Z, to elucidate their strategic roles in general elections, and to project the future configuration of their political participation. Employing a qualitative approach with a systematic literature review design, the research synthesizes scholarly articles, policy reports, and empirical studies on youth politics, digital participation, and democratic practices in Indonesia. Data were analyzed through iterative coding, thematic categorization, and interpretive synthesis to capture patterns of engagement both in formal and non-formal arenas. The findings reveal that Generation Z is not confined to the role of voters; they also act as digital campaigners, political influencers, grassroots mobilizers, and policy advocates who leverage social media platforms to frame issues, shape narratives, and influence public opinion. They demonstrate a combination of skepticism toward traditional political institutions and a strong propensity for issue-based activism, particularly on governance, social justice, and environmental concerns. The study concludes that Generation Z possesses substantial potential to recalibrate public policy and democratic accountability through sustained digital mobilization and hybrid forms of participation that bridge online and offline spaces. The novelty of this research lies in its comprehensive mapping of Indonesian Generation Z’s political engagement patterns specifically through the lens of digital political behavior, which has previously been examined only in fragmented or partial ways. The study contributes theoretically by advancing the discourse on digital democracy in the Global South and practically by offering evidence-based insights for political actors, electoral managers, and policymakers seeking to meaningfully engage young voters as partners in democratic consolidation.